2014
DOI: 10.1007/s13157-014-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Plant Community Hydrology Using Large-Extent, Long-Term Data

Abstract: Large-extent vegetation datasets that co-occur with long-term hydrology data provide new ways to develop biologically meaningful hydrologic variables and to determine plant community responses to hydrology. We analyzed the suitability of different hydrological variables to predict vegetation in two water conservation areas (WCAs) in the Florida Everglades, USA, and developed metrics to define realized hydrologic optima and tolerances.Using vegetation data spatially co-located with long-term hydrological record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Although a macrocosm study indicated that C . jamaicense has broad inundation and water depth tolerances and grew best in areas with relatively deep water (maximum depth 94 cm; Serna et al ), field (Childers et al ), mesocosm (Miao & Zou ), and modeling (Gann & Richards ) studies have indicated that C . jamaicense growth and productivity declined with increased water depth and hydroperiod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a macrocosm study indicated that C . jamaicense has broad inundation and water depth tolerances and grew best in areas with relatively deep water (maximum depth 94 cm; Serna et al ), field (Childers et al ), mesocosm (Miao & Zou ), and modeling (Gann & Richards ) studies have indicated that C . jamaicense growth and productivity declined with increased water depth and hydroperiod.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore probable that salinity at our brackish marsh sites was stressful to this species. Although a macrocosm study indicated that C. jamaicense has broad inundation and water depth tolerances and grew best in areas with relatively deep water (maximum depth 94 cm; Serna et al 2015), field (Childers et al 2006), mesocosm (Miao & Zou 2012), and modeling (Gann & Richards 2015) studies have indicated that C. jamaicense growth and productivity declined with increased water depth and hydroperiod. We were not able to assess the possible role of water depth and flooding duration as factors limiting C. jamaicense growth because we have just a single depth measurement per quadrat per sampling event.…”
Section: Areamentioning
confidence: 99%
“…Conditional densities for each community type along each gradient (elevation, distance to coast, May groundwater salinity, and November groundwater salinity) were derived using the package 'sm' in R v.3.1.2 (R core team, 2014). These plots provided information on the proportional abundance of each community compared to all other communities along each point of the environmental gradient (Gann and Richards, 2015).…”
Section: Prediction Of Community Typesmentioning
confidence: 99%